Trans-Tasman Cumulative Effects Management: A Comparative Study - Davies, Kathryn K.; Fisher, Karen T.; Couzens, Gemma; Allison, Andrew; van Putten, Elizabeth Ingrid; Dambacher, Jeffrey M.; Foley, Melissa; Lundquist, Carolyn J. (Frontiers in Marine Science, 2020)
Managing the cumulative effects that arise from human and natural stressors is one of the most urgent and complex problems facing coastal and marine decision makers today. In the absence of effective processes, models, and political will, decision-makers struggle to implement management strategies that effectively tackle cumulative effects. Emerging efforts to address cumulative effects provide a timely opportunity to assess the efficacy of a range of management strategies operating at different scales and in different legislative and cultural contexts. Using primarily qualitative methodologies including literature reviews, focus groups, and workshops, this paper compares cumulative effects approaches within the Reef 2050 Plan for the Great Barrier Reef Marine Park (GBRMP), Australia, with those in Aotearoa New Zealand (Aotearoa NZ). Both case studies illustrate that cumulative effects management is especially complicated by: fragmented legislative regimes and institutions that cannot account for cross-scale or cross-sector interactions; chronic data scarcity and high levels of uncertainty that make system-based assessments and predictions challenging; and often conflicting societal and economic expectations, values, and rights that are poorly integrated into management decision-making. By considering how these two cases align with transformational change characteristics, we draw several conclusions and establish priority actions regarding 1) how to mobilise resources and political will to address CE, 2) how to deal with data scarcity and uncertainty, and 3) how to promote comprehensive and inclusive CE management of coastal and marine areas.